All-solid-state dry-process negative electrode sheet and all-solid-state battery
By combining fibrous binder and non-fibrous binder in an all-solid dry negative electrode sheet, the interface debonding problem caused by volume expansion of silicon-based negative electrode materials is solved, and the cycle stability and energy of the battery are improved Density, achieving high-performance all-solid-state battery.
Patent Information
- Application Number
- CN202411074275.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-07
AI Technical Summary
The huge volume expansion of the silicon-based negative electrode material after lithium is embedded causes debonding with the solid electrolyte interface, affecting the performance and safety of all-solid-state batteries. Fibrous adhesives such as PTFE cannot guarantee sufficient interface adhesion.
By combining fibrous binder and non-fibrous binder, the interface bonding effect is enhanced by introducing non-fibrous binder into the second dry negative electrode layer of the all-solid dry negative electrode sheet, and the interface bonding effect is improved through Gradient design optimizes the ratio and layer thickness ratio of fibrous adhesives to non-fibrous adhesives to ensure consistent interface durability.
It realizes the long cycle life and high rate performance of all solid-state batteries, improves the energy density and cycle stability of the battery, and avoids the problem of interface debonding.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and more specifically, to an all-solid-state dry-process negative electrode sheet and an all-solid-state battery. Background Art
[0002] In the rapid development of the new energy field, the development of batteries such as lithium-ion batteries is particularly important, and all-solid-state batteries are regarded as one of the final forms of commercial lithium-ion batteries. In addition, the development of all-solid-state batteries can effectively avoid the risks of thermal runaway and flammability of traditional lithium-ion batteries. Sulfide solid electrolytes have high ionic conductivity and ductility. When they are matched with ternary negative electrodes and high theoretical capacity negative electrodes, the energy density of the assembled battery can reach 500 Wh / kg. Among all high theoretical capacity negative electrodes, silicon is the most attractive choice because of its high theoretical specific capacity (4200 mAh / g), abundant reserves, and the advantages of low cost and environmental protection.
[0003] However, silicon-based materials have problems such as poor conductivity and volume expansion. The all-solid-state dry-process negative electrode sheet is composed of negative electrode active materials and solid electrolytes. The contact area between them is increased by mixing the negative electrode active materials and the solid electrolyte to improve the ion transfer efficiency. However, for silicon-based negative electrode materials, huge volume expansion (up to 360%) occurs after lithium insertion, which easily leads to interface debonding between the negative electrode material and the solid electrolyte, resulting in failure of the electrode structure during charging and discharging. Interface debonding is the main cause of performance degradation and safety issues of all-solid-state batteries. During charging, lithium ions move from the positive electrode to the negative electrode, and the negative electrode active material particles close to the positive electrode side are first intercalated with lithium; similarly, during discharge, the negative electrode active material particles closer to the positive electrode side are more delithiated, indicating that the negative electrode active material particles closer to the positive electrode side face more serious interface debonding problems. Therefore, it is necessary to improve the consistency of the interface durability between the negative electrode active material and the solid electrolyte in the thickness dimension of the negative electrode sheet.
[0004] In summary, the defects in the prior art are:
[0005] 1) For silicon-based negative electrode materials, a huge volume expansion (up to 360%) will occur after lithium insertion, which can easily lead to interface debonding between the negative electrode material and the solid electrolyte, thereby causing the electrode structure to fail during the charging and discharging process. It can be seen that interface debonding is the main cause of performance degradation and safety issues of all-solid-state batteries.
[0006] 2) Fibrous binder defects: The representative fibrous binder used in the dry process is polytetrafluoroethylene (PTFE), but PTFE cannot ensure sufficient interfacial adhesion between the negative electrode active material, solid electrolyte and conductive agent. The dry binder PTFE will react with the lithium ions on the surface of the negative electrode to generate lithium fluoride, weakening the bonding effect. Therefore, further improvement is needed. Summary of the invention
[0007] This application combines fibrous binders and non-fibrous binders to maintain good consistency of the interface durability of the components inside the all-solid-state dry-process negative electrode plate throughout the entire thickness. Since fibrous binders such as PTFE (polytetrafluoroethylene) react with lithium ions on the surface of the dry-process negative electrode plate to form lithium fluoride, weakening the bonding effect, the introduction of non-fibrous binders into the dry-process negative electrode plate can improve the bonding effect. This design can maintain good interface contact between the components inside the all-solid-state dry-process negative electrode plate during battery cycling, thereby developing a high-energy-density all-solid-state battery with long cycle life and high-rate performance.
[0008] Some embodiments of the present application provide an all-solid-state dry-process negative electrode sheet, comprising: a negative electrode current collector; a first dry-process negative electrode layer, arranged close to the negative electrode current collector; and a second dry-process negative electrode layer, arranged away from the negative electrode current collector relative to the first dry-process negative electrode layer, wherein the first dry-process negative electrode layer comprises a first fibrous binder, and the second dry-process negative electrode layer comprises a second fibrous binder and a non-fibrous binder. In some embodiments, the first fibrous binder is the same as or different from the second fibrous binder. In the present application, by compounding a fibrous binder and a non-fibrous binder in the second dry-process negative electrode layer, the interface durability of each component inside the all-solid-state dry-process negative electrode sheet can be made the same throughout the thickness. This design can maintain good interface contact between the components inside the all-solid-state dry-process negative electrode sheet during the cycle of the all-solid-state battery, so that the all-solid-state battery has a long cycle life and high rate performance.
[0009] In some embodiments, the mass content of the first fibrous binder in the first dry-process negative electrode layer is 1%-2%. In some embodiments, in the second dry-process negative electrode layer, the mass content of the non-fibrous binder is 0.6%~4%. In some embodiments, the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is 1:1.5~4, optionally, the ratio is in the range of 1:1.5~3.2, further optionally, the ratio is in the range of 1:2~3, and the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1~2. In some embodiments, the ratio of the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer to the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1.4~1.6. In the present application, a reasonable mass ratio of fibrous binder to non-fibrous binder is designed in the second dry-process negative electrode layer, and the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is adjusted. This can improve the battery energy density while promoting the uniformity of the reaction kinetics in the depth direction of the dry-process negative electrode sheet, making the interface durability of each component inside the all-solid-state dry-process negative electrode sheet the same throughout the thickness, thereby improving the corresponding all-solid-state battery performance and cycle stability.
[0010] In some embodiments, the first dry-process negative electrode layer includes a first negative electrode active material, and the second dry-process negative electrode layer includes a second negative electrode active material, wherein the mass content of the first negative electrode active material is W1 based on the mass of the first dry-process negative electrode layer, and the mass content of the second negative electrode active material is W2 based on the mass of the second dry-process negative electrode layer, wherein W1 is 40% to 60%, and W1:W2 is 1:1 to 1.3. In some embodiments, the first negative electrode active material is different from the second negative electrode active material.
[0011] In some embodiments, the first negative electrode active material includes a silicon-carbon alloy with a first silicon doping amount, and the second active material includes a silicon-carbon alloy with a second silicon doping amount and a third silicon-carbon alloy, wherein the first silicon doping amount is less than the second silicon doping amount.
[0012] In some embodiments, the particle size of the silicon-carbon alloy with the second silicon doping amount is greater than the particle size of the third silicon-carbon alloy, wherein, in the volume-based particle size distribution, the silicon-carbon alloy with the first silicon doping amount has a particle size of 12~14μm starting from the small particle size side and reaching 50% of the volume accumulation; in the volume-based particle size distribution, the silicon-carbon alloy with the second silicon doping amount has a particle size of 12~14μm starting from the small particle size side and reaching 50% of the volume accumulation; and in the volume-based particle size distribution, the particle size of the third silicon-carbon alloy starting from the small particle size side and reaching 50% of the volume accumulation is 7~9μm, wherein the all-solid-state dry-process negative electrode plate also includes: a solid electrolyte, wherein, in the volume-based particle size distribution, the solid electrolyte has a particle size of 2~4μm starting from the small particle size side and reaching 50% of the volume accumulation.
[0013] In some embodiments, based on the mass of the silicon-carbon alloy with the first silicon doping amount, the mass content of the silicon element in the silicon-carbon alloy with the first silicon doping amount is W3, and based on the mass of the silicon-carbon alloy with the second silicon doping amount, the mass content of the silicon element in the silicon-carbon alloy with the second silicon doping amount is W4, wherein W3 is 10%-30%, and W3:W4 is 1:1.8~2.2.
[0014] In some embodiments, the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is 1:2-3.
[0015] In some embodiments, the first dry-process negative electrode layer and the second dry-process negative electrode layer also include a conductive agent, wherein the mass ratio of the first negative electrode active material, the solid electrolyte, the conductive agent and the first fibrous binder in the first dry-process negative electrode layer is 40~60:30~50:1~10:1~2, and the mass ratio of the second negative electrode active material, the solid electrolyte, the conductive agent, the second fibrous binder and the non-fibrous binder in the second dry-process negative electrode layer is 40~60:30~50:1~10:1~5.
[0016] In some embodiments, the non-fibrous binder includes at least one of sodium carboxymethyl cellulose, LA type aqueous electrode binder, styrene-butadiene rubber, sodium alginate, polyacrylonitrile, polyurethane, polyacrylic acid or polyvinylidene fluoride.
[0017] In some embodiments, the fibrous binder includes at least one of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, polypropylene, polyethylene, ethylene-octene copolymer, or polyimide.
[0018] Other embodiments of the present application also provide an all-solid-state battery, including the above-mentioned all-solid-state dry-process negative electrode plate.
[0019] The present application adopts a gradient-designed all-solid-state dry-process negative electrode plate, that is, a first dry-process negative electrode layer and a second dry-process negative electrode layer are adopted, and the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is 1:1.5~4, especially the ratio is in the range of 1:2~3, and the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is in the range of 1:1~2. When the ratio of the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer to the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1.4~1.6, the number of cycles of the battery at room temperature can be effectively improved, thereby improving the battery performance and cycle stability. DETAILED DESCRIPTION
[0020] In the field of new energy, the application of batteries is becoming more and more important. In the research of batteries, the development of all-solid-state batteries is becoming more and more important. Based on this, the present application provides an all-solid-state dry-process negative electrode sheet and an all-solid-state battery. For the all-solid-state dry-process negative electrode sheet, by combining a fibrous binder and a non-fibrous binder, the interface durability of each component inside the all-solid-state dry-process negative electrode sheet is the same throughout the thickness. The all-solid-state dry-process negative electrode sheet includes a negative electrode current collector; a first dry-process negative electrode layer arranged close to the negative electrode current collector; and a second dry-process negative electrode layer arranged away from the negative electrode current collector relative to the first dry-process negative electrode layer, wherein the first dry-process negative electrode layer includes a first fibrous binder, and the second dry-process negative electrode layer includes a second fibrous binder and a non-fibrous binder. Further, the non-fibrous binder can significantly improve the interfacial bonding force of each component in the all-solid-state dry-process negative electrode sheet, while the fibrous binder such as PTFE will react with the lithium ions on the surface of the negative electrode to generate lithium fluoride, weakening the bonding effect. The introduction of a non-fibrous binder into the dry-process negative electrode sheet can improve the bonding effect. By compounding the fibrous binder and the non-fibrous binder in the second dry-process negative electrode layer, the interface durability of each component inside the all-solid-state dry-process negative electrode sheet can be made the same throughout the thickness. This design can maintain good interface contact between each component inside the all-solid-state dry-process negative electrode sheet during the cycle of the all-solid-state battery, thereby enabling the all-solid-state battery to have a long cycle life and high rate performance.
[0021] Generally, non-fibrous binder: a binder that cannot be fiberized, such as sodium carboxymethyl cellulose, LA type aqueous electrode binder, styrene-butadiene rubber, sodium alginate, polyacrylonitrile, polyurethane, polyacrylic acid, polyvinylidene fluoride, etc., and fibrous binder: a binder that can be fiberized, such as polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, polypropylene, polyethylene, ethylene-octene copolymer, polyimide, etc. In the above-mentioned all-solid-state dry-process negative electrode sheet, the non-fibrous binder includes one or more of styrene-butadiene rubber, sodium alginate, polyacrylonitrile, polyurethane, polyacrylic acid, polyvinylidene fluoride, and polyvinylidene fluoride can be selected. In addition, the first fibrous binder and the second fibrous binder include, but are not limited to, one or more of polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer, polypropylene, polyethylene, ethylene-octene copolymer, polyimide, and polytetrafluoroethylene (PTFE) can be selected. In some embodiments, the first fibrous binder is the same as or different from the second fibrous binder.
[0022] In some embodiments, the mass content of the first fibrous binder in the first dry-process negative electrode layer is 1%-2%. In some embodiments, in the second dry-process negative electrode layer, the mass content of the non-fibrous binder is 0.6%-4%, and the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is 1:1.5-4, optionally 1:1.5-3.2, and further optionally 1:2-3, the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1-2, and the ratio of the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer to the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1.4-1.6, and optionally 1:1.5. Designing a reasonable mass ratio of fibrous binder to non-fibrous binder in the second dry-process negative electrode layer and adjusting the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer can improve the battery energy density while promoting the uniformity of the reaction kinetics in the depth direction of the dry-process negative electrode sheet, making the interface durability of each component inside the all-solid-state dry-process negative electrode sheet the same throughout the thickness, thereby improving the corresponding all-solid-state battery performance and cycle stability.
[0023] In a further embodiment, the first dry-process negative electrode layer includes a first negative electrode active material, and the second dry-process negative electrode layer includes a second negative electrode active material, wherein the mass content of the first negative electrode active material is W1 based on the mass of the first dry-process negative electrode layer, and the mass content of the second negative electrode active material is W2 based on the mass of the second dry-process negative electrode layer, wherein W1 is 40% to 60%, and W1:W2 is 1:1 to 1.3. In some embodiments, the first negative electrode active material is different from the second negative electrode active material. Specifically, the first negative electrode active material includes a silicon-carbon alloy with a first silicon doping amount, and the second active material includes a silicon-carbon alloy with a second silicon doping amount and a third silicon-carbon alloy, wherein the first silicon doping amount is less than the second silicon doping amount. In addition, the particle size of the silicon-carbon alloy with the second silicon doping amount is larger than the particle size of the third silicon-carbon alloy, wherein, in the volume-based particle size distribution, the particle size (D50) of the silicon-carbon alloy with the first silicon doping amount starting from the small particle size side and reaching 50% of the volume accumulation is 12~14μm; in the volume-based particle size distribution, the particle size of the silicon-carbon alloy with the second silicon doping amount starting from the small particle size side and reaching 50% of the volume accumulation is 12~14μm; and in the volume-based particle size distribution, the particle size of the third silicon-carbon alloy starting from the small particle size side and reaching 50% of the volume accumulation is 7~9μm. In some embodiments, the all-solid-state dry-process negative electrode plate also includes: a solid electrolyte, wherein, in the volume-based particle size distribution, the particle size of the solid electrolyte starting from the small particle size side and reaching 50% of the volume accumulation is 2~4μm. In a further embodiment, based on the mass of the silicon-carbon alloy with the first silicon doping amount, the mass content of silicon in the silicon-carbon alloy with the first silicon doping amount is W3, and based on the mass of the silicon-carbon alloy with the second silicon doping amount, the mass content of silicon in the silicon-carbon alloy with the second silicon doping amount is W4, wherein W3 is 10%-30%, and W3:W4 is 1:1.8~2.2. That is, the negative electrode active material in the first dry-process negative electrode layer is a silicon-carbon alloy with a lower silicon doping amount, D50=12~14μm; the negative electrode active material in the second dry-process negative electrode layer is a silicon-carbon alloy with a higher silicon doping amount and small-particle silicon carbon, the D50 of the silicon-carbon alloy with a higher silicon doping amount is 12~14μm, the D50 of the small-particle silicon carbon is 7~9μm, and the ratio of the silicon mass content of the silicon-carbon alloy with a lower silicon doping amount to the silicon-carbon alloy with a higher silicon doping amount is 1:1.8~2.2.
[0024] The inventors discovered in their research that by using the above negative electrode active material mass content ratio and negative electrode active material silicon mass content ratio in the first dry-process negative electrode layer and the second dry-process negative electrode layer, and at the same time using a compound strategy of large and small particle negative electrode active materials in the second dry-process negative electrode layer, the surface capacity of the all-solid-state dry-process negative electrode sheet and the utilization rate of the negative electrode active material can be greatly improved, thereby improving the energy density of the battery.
[0025] In some specific embodiments, the negative electrode active material may be a graphite material, a silicon material, or a composite material formed by a combination of the two. Examples of graphite materials include natural graphite (block graphite, flake graphite, earthy graphite), artificial graphite (single crystal graphite, polycrystalline graphite, pyrolytic graphite, graphite fiber, etc.). Examples of silicon materials include, but are not limited to, crystalline silicon, amorphous silicon, and organic silicon.
[0026] Furthermore, in some embodiments, the type of the solid electrolyte is one or more of an oxide solid electrolyte, a sulfide solid electrolyte, and a halide solid electrolyte.
[0027] In the present application, the type of the conductive agent in the all-solid-state dry-process negative electrode plate is one or more of graphite, graphene, carbon black, carbon fiber and carbon nanotube. Optionally, the conductive agent includes carbon black and carbon fiber; the mass ratio of carbon black to carbon fiber is 1:(0.2~1.5); optionally 1:1. Further optionally, the carbon black is conductive carbon black (super p); the carbon fiber is at least one of carbon nanofiber (CNF), vapor grown carbon fiber (VGCF), and vapor grown carbon nanofiber (VGCNF).
[0028] In summary, the all-solid-state dry-process negative electrode sheet may include a negative electrode active material, a solid electrolyte, a conductive agent and a binder. Optionally, the mass ratio of the first negative electrode active material, the solid electrolyte, the conductive agent and the first fibrous binder in the first dry-process negative electrode layer is (40~60): (30~50): (1~10): (1~2), and the mass ratio of the second negative electrode active material, the solid electrolyte, the conductive agent and the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is (40~60): (30~50): (1~10): (1~5). In addition, the mass ratio of the negative electrode active material, the solid electrolyte, the conductive agent and the binder in the all-solid-state dry-process negative electrode sheet is (40~60): (30~50): (1~10): (1~5).
[0029] Other embodiments of the present application also provide an all-solid-state battery, including the above-mentioned all-solid-state dry-process negative electrode plate.
[0030] In addition, some other embodiments of the present application also provide a method for preparing the above-mentioned all-solid-state dry-process negative electrode sheet, comprising the following steps:
[0031] S1. The corresponding amount of negative electrode active material, solid electrolyte, conductive agent and fibrous binder are mixed in a glove box to form a mixture. The mixture is then ball-milled to make the binder fibrous to obtain a mass mixture. The mass mixture is repeatedly rolled at a corresponding temperature to a certain thickness to obtain the first dry-process negative electrode layer;
[0032] S2. The corresponding amount of negative electrode active material, solid electrolyte, conductive agent, fibrous binder and non-fibrous binder are mixed in a glove box to form a mixture, and then the mixture is ball-milled to make the fibrous binder fibrous to obtain a mass mixture. The mass mixture is repeatedly rolled at a corresponding temperature to a certain thickness to obtain a second dry-process negative electrode layer;
[0033] S3. Roll-compounding the first dry-process negative electrode layer and the second dry-process negative electrode layer to a certain thickness at a corresponding temperature, and compounding with the negative electrode current collector, and then hot-pressing at a high temperature for a period of time to obtain the above-mentioned all-solid-state dry-process negative electrode sheet.
[0034] Optionally, in the above steps S1 and S2, the rotation speed during ball milling is 100-1000 rpm, the mixing time is 0.5-3h, the diameter of the ball milling zirconium beads is 5-20 mm, and the ball-to-material ratio is (20-50): 1. The applicant has found that the above ball milling conditions can make the raw materials mixed more uniformly, thereby improving the interface compatibility between the components; at the same time, after high-energy ball milling, the heat generated makes the fibrous binder more easily fibrillated, and the fibrous binder forms a three-dimensional cross-linked network inside the negative electrode sheet to effectively fix the components.
[0035] Further optionally, the rotation speed of the ball milling mixing is 500 rpm, the ball milling time is 2 h, the diameter of the ball milling zirconium beads is 10 mm, and the ball-to-material ratio is 30:1.
[0036] The rolling temperature is 60~150 ℃; the temperature of the above hot pressing is not limited, as long as it is higher than the melting point of the non-fibrous binder and does not affect the performance of other negative electrode plate components, such as the hot pressing temperature is 150~250 ℃, the hot pressing time is 0.5~2 h, and the hot pressing pressure is 50~500 MPa. The applicant found that after the non-fibrous binder is mixed, a layer of non-fibrous binder particles is adsorbed on the surface of the negative electrode active material particles and the solid electrolyte particles. After hot pressing, the non-fibrous binder can form a uniform film on its surface, thereby enhancing the bonding force to strengthen the interface contact.
[0037] In addition, the negative electrode current collector is a carbon-coated copper foil with a thickness of 6-20 μm. The surface loading of the final all-solid-state dry-process negative electrode sheet is 1-10 mAh cm -2 .
[0038] The following takes all-solid-state lithium-ion batteries as an example
[0039] All-solid-state dry-process negative electrode
[0040] The all-solid-state dry-process negative electrode sheet in the all-solid-state battery provided in the present application includes a negative electrode current collector; a first dry-process negative electrode layer arranged close to the negative electrode current collector; and a second dry-process negative electrode layer arranged away from the negative electrode current collector relative to the first dry-process negative electrode layer, wherein the first dry-process negative electrode layer includes a first fibrous binder, and the second dry-process negative electrode layer includes a second fibrous binder and a non-fibrous binder. The non-fibrous binder includes one or more of styrene-butadiene rubber, sodium alginate, polyacrylonitrile, polyurethane, polyacrylic acid, and polyvinylidene fluoride, which can be selected as polyvinylidene fluoride. In addition, the first fibrous binder and the second fibrous binder include, but are not limited to, one or more of polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer, polypropylene, polyethylene, ethylene-octene copolymer, and polyimide, which can be selected as polytetrafluoroethylene (PTFE). In some embodiments, the first fibrous binder is the same as or different from the second fibrous binder. In other words, the all-solid-state dry-process negative electrode plate includes a negative electrode current collector commonly used in the art and a negative electrode active material, a solid electrolyte, a conductive agent and a binder arranged on the negative electrode current collector. Optionally, the mass ratio of the negative electrode active material, the solid electrolyte, the conductive agent and the binder in the all-solid-state dry-process negative electrode plate is (40~60): (30~50): (1~5): (1~5).
[0041] In addition, the negative electrode current collector may be a carbon-coated copper foil current collector, however, other negative electrode current collectors commonly used in the art may be used.
[0042] Counter electrode
[0043] The electrode plate can be made of indium, lithium, indium, aluminum or an alloy of at least two of the above metals.
[0044] Solid electrolyte layer
[0045] The solid electrolyte layer is composed of a solid electrolyte and a fibrous binder, wherein the solid electrolyte is one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte, and the fibrous binder is one or more of polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer, polypropylene, polyethylene, ethylene-octene copolymer, and polyimide.
[0046] The preparation method of the solid electrolyte layer is as follows: a corresponding amount of solid electrolyte and a fibrous binder are mixed in a glove box to form a mixture. The mixture is then ball-milled to make the binder fibrous to obtain a mass-shaped mixture. The mass-shaped mixture is repeatedly rolled at a corresponding temperature to a certain thickness to obtain a solid electrolyte layer.
[0047] Optionally, the mass ratio of the solid electrolyte to the fibrous binder in the solid electrolyte layer is 90-100:0.5-10.
[0048] The thickness of the solid electrolyte layer can be selected to be 20-200 μm.
[0049] All-solid-state battery
[0050] The all-solid-state dry-process negative electrode sheet, the solid electrolyte layer and the counter electrode sheet are sequentially placed into the mold for assembly; after assembly, pressurization is applied and the nut at the top of the column is tightened with a constant pressure to obtain an all-solid-state lithium-ion battery.
[0051] Note: The assembly process is completed in a glove box with an argon atmosphere, and the particle diameters of the corresponding powders of the all-solid-state dry-process negative electrode sheet, solid electrolyte layer and counter electrode sheet are kept consistent.
[0052] It should be noted that the all-solid-state battery prepared by the above method is an all-solid-state lithium-ion battery. However, the battery prepared in this application may also be an all-solid-state sodium-ion battery or a potassium-ion battery.
[0053] Those skilled in the art will understand that the above-described method for preparing the battery is only an example, and other methods commonly used in the art may be used without departing from the contents disclosed in the present application.
[0054] The reagents and raw materials used in the present invention are commercially available.
[0055] The present invention has no special requirements for the assembly method of the above-mentioned battery, and an assembly method familiar to those skilled in the art can be used. In addition, the above-mentioned technical solution can be applied not only to commonly used all-solid-state lithium-ion batteries, but also to all-solid-state sodium-ion batteries, all-solid-state potassium-ion batteries and other types of kinetic batteries.
[0056] Some specific embodiments and comparative examples are listed below to better illustrate the present application.
[0057] Example 1
[0058] All-solid-state dry-process negative electrode
[0059] The all-solid-state dry-process negative electrode comprises a carbon-coated copper foil current collector, a first dry-process negative electrode layer arranged close to the current collector; and a second dry-process negative electrode layer arranged away from the current collector relative to the first dry-process negative electrode layer.
[0060] Specifically, the first dry-process negative electrode layer includes a first negative electrode active material, a solid electrolyte, a conductive agent and a fibrous binder; wherein the mass ratio of the first negative electrode active material, the solid electrolyte, the conductive agent and the first fibrous binder is 49:45:5:1.
[0061] The second dry-process negative electrode layer includes a negative electrode active material, a solid electrolyte, a conductive agent, a fibrous binder and a non-fibrous binder; wherein the mass ratio of the second negative electrode active material, the solid electrolyte, the conductive agent, the second fibrous binder and the non-fibrous binder is 58:33:5:1:3.
[0062] The first negative electrode active material in the first dry-process negative electrode layer is a silicon-carbon alloy with a low silicon doping content; it comes from Guangdong Candlelight New Energy Technology Co., Ltd., the model is silicon-carbon alloy 650, the silicon content is 13%, and D50 is 13 μm; the second negative electrode active material in the second dry-process negative electrode layer is a silicon-carbon alloy with a high silicon doping content and small-particle silicon carbon, the silicon-carbon alloy with a high silicon doping content comes from Guangdong Candlelight New Energy Technology Co., Ltd., the model is silicon-carbon alloy 1200, the silicon content is 26%, the D50 is 13 μm, and the small-particle silicon carbon D50 is 8 μm;
[0063] The solid electrolyte is a sulfide solid electrolyte, specifically Li6PS5Cl; it comes from Beijing Mingchen Zhonghuan Technology Co., Ltd., model LPSCl-Li6PS5Cl1, D50=2.5 μm.
[0064] The conductive agent is super p (Tianjin Youmeng Chemical Technology Co., Ltd., super p) and VGCF (Showa Denko K.K., VGCF-H) in a mass ratio of 1:1.
[0065] The fibrous binder is PTFE, which comes from Daikin Fluorochemical (China) Co., Ltd., model M-392.
[0066] The non-fibrous binder is PVDF, which is from Alfa and has the model number of Alfa Aesar 44080.
[0067] The preparation steps of the all-solid-state dry-process negative electrode are as follows:
[0068] S1. Mix corresponding amounts of silicon-carbon alloy 650, Li6PS5Cl, conductive agent and PTFE in a glove box to form a mixture. Then, the mixture is ball-milled to make the binder fibrous to obtain a mass-like mixture. The mass-like mixture is repeatedly rolled at 80°C to a certain thickness to obtain the first dry-process negative electrode layer;
[0069] S2. The corresponding amounts of silicon-carbon alloy 1200, Li6PS5Cl, conductive agent, PTFE and PVDF are mixed in a glove box to form a mixture, and then the mixture is ball-milled to make the fibrous binder fibrous to obtain a mass mixture. The mass mixture is repeatedly rolled at 80°C to a certain thickness to obtain a second dry-process negative electrode layer;
[0070] S3. The first dry-process negative electrode layer and the second dry-process negative electrode layer are rolled and laminated at 80°C to a certain thickness, and then laminated with a carbon-coated copper foil current collector, and then hot-pressed at 200°C for 1 h under a pressure of 100 MPa to obtain the all-solid-state dry-process negative electrode sheet. The final all-solid-state dry-process negative electrode sheet has a surface capacity of 10 mAh cm -2 .
[0071] The thickness of the first dry-process negative electrode layer prepared is 20 μm, and the thickness of the second dry-process negative electrode layer is 40 μm.
[0072] The ball milling speed was 500 rpm, the ball milling time was 2 h, the diameter of the zirconium beads was 10 mm, and the ball-to-material ratio was 30:1.
[0073] Counter electrode
[0074] The counter electrode is a lithium indium alloy sheet (the diameter of the lithium indium alloy sheet powder particles is φ=10 mm).
[0075] Solid electrolyte layer
[0076] The solid electrolyte layer is composed of a solid electrolyte (Li6PS5Cl) and a fibrous binder (PTFE), and the mass ratio of the solid electrolyte (Li6PS5Cl) to the fibrous binder (PTFE) is 99:1.
[0077] The preparation steps of all-solid-state lithium-ion batteries are:
[0078] The all-solid-state dry-process negative electrode sheet, solid electrolyte layer and lithium-indium alloy sheet are sequentially placed into the mold for assembly; after assembly, the pressure is increased to 100 MPa and the nut at the top of the column is tightened to maintain a constant pressure to obtain an all-solid-state lithium-ion battery.
[0079] Note: The assembly process is completed in a glove box with an argon atmosphere. The particle diameters of the corresponding powders of the all-solid-state dry-process negative electrode sheet, solid electrolyte layer and lithium-indium alloy sheet are all 10 mm.
[0080] Example 2
[0081] The preparation method is consistent with that of Example 1, except that the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer in Example 2 is 1:2, and the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1.3, wherein the sum of the thicknesses of the first dry-process negative electrode layer and the second dry-process negative electrode layer is 60 μm.
[0082] Example 3
[0083] The preparation method is consistent with that in Example 1, except that the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer in Example 3 is 1:2.5, and the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1.7, wherein the sum of the thicknesses of the first dry-process negative electrode layer and the second dry-process negative electrode layer is 60 μm.
[0084] Example 4
[0085] The preparation method is consistent with that of Example 1, except that the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer in Example 4 is 1:1.5, and the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1, wherein the sum of the thicknesses of the first dry-process negative electrode layer and the second dry-process negative electrode layer is 60 μm.
[0086] Example 5
[0087] The preparation method is consistent with that of Example 1, except that the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer in Example 5 is 1:3.2, and the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:2, wherein the sum of the thicknesses of the first dry-process negative electrode layer and the second dry-process negative electrode layer is 60 μm.
[0088] Example 6
[0089] The preparation method is consistent with that of Example 1, except that the mass ratio of the first negative electrode active material, solid electrolyte, conductive agent and first fibrous binder in Example 6 is 49:45:10:1, and the mass ratio of the second negative electrode active material, solid electrolyte, conductive agent, second fibrous binder and non-fibrous binder is 58:33:10:1:3.
[0090] Example 7
[0091] The preparation method is consistent with that of Example 1, except that the mass ratio of the first negative electrode active material, solid electrolyte, conductive agent and first fibrous binder in Example 7 is 49:45:1:1, and the mass ratio of the second negative electrode active material, solid electrolyte, conductive agent, second fibrous binder and non-fibrous binder is 58:33:1:1:3.
[0092] Example 8
[0093] The preparation method is consistent with that of Example 1, except that the mass ratio of the first negative electrode active material, the solid electrolyte, the conductive agent and the first fibrous binder in Example 8 is 49:45:5:2, and the mass ratio of the second negative electrode active material, the solid electrolyte, the conductive agent, the second fibrous binder and the non-fibrous binder is 58:33:5:1:3. The thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:2.
[0094] Example 9
[0095] The preparation method is consistent with that in Example 1, except that the first negative electrode active material in the first dry-process negative electrode layer in Example 9 is a silicon-carbon alloy with a low silicon doping amount, and D50 is 12μm; the second negative electrode active material in the second dry-process negative electrode layer is a silicon-carbon alloy with a high silicon doping amount and small-particle silicon carbon, and the silicon-carbon alloy with a high silicon doping amount has a D50 of 12μm, and the small-particle silicon carbon has a D50 of 7μm.
[0096] Example 10
[0097] The preparation method is consistent with that in Example 1, except that the first negative electrode active material in the first dry-process negative electrode layer in Example 10 is a silicon-carbon alloy with a low silicon doping amount, and D50 is 14μm; the second negative electrode active material in the second dry-process negative electrode layer is a silicon-carbon alloy with a high silicon doping amount and small-particle silicon carbon, and the silicon-carbon alloy with a high silicon doping amount has a D50 of 14μm, and the small-particle silicon carbon has a D50 of 9μm.
[0098] Embodiment 11
[0099] The preparation method is consistent with that in Example 1, except that the first negative electrode active material in the first dry-process negative electrode layer in Example 11 is a silicon-carbon alloy with a low silicon doping amount, and D50 is 12μm; the second negative electrode active material in the second dry-process negative electrode layer is a silicon-carbon alloy with a high silicon doping amount and small-particle silicon carbon, and the silicon-carbon alloy with a high silicon doping amount has a D50 of 13μm, and the small-particle silicon carbon has a D50 of 8μm.
[0100] Example 12
[0101] The preparation method is consistent with that of Example 1, except that the D50 of the solid electrolyte in Example 12 is 2 μm.
[0102] Example 13
[0103] The preparation method is consistent with that of Example 1, except that the D50 of the solid electrolyte in Example 13 is 3 μm.
[0104] Embodiment 14
[0105] The preparation method is consistent with that of Example 1, except that the D50 of the solid electrolyte in Example 14 is 4 μm.
[0106] Embodiment 15
[0107] The preparation method is consistent with that in Example 1, except that the first negative electrode active material in the first dry-process negative electrode layer in Example 15 is a silicon-carbon alloy with a low silicon doping amount, and the silicon content is 13%; the second negative electrode active material in the second dry-process negative electrode layer is a silicon-carbon alloy with a high silicon doping amount and small-particle silicon carbon, and the silicon content of the silicon-carbon alloy with a high silicon doping amount is 24%.
[0108] Example 16
[0109] The preparation method is consistent with that in Example 1, except that the first negative electrode active material in the first dry-process negative electrode layer in Example 16 is a silicon-carbon alloy with a low silicon doping amount, and the silicon content is 13%; the second negative electrode active material in the second dry-process negative electrode layer is a silicon-carbon alloy with a high silicon doping amount and small-particle silicon carbon, and the silicon content of the silicon-carbon alloy with a high silicon doping amount is 28%.
[0110] Comparative Example 1
[0111] The preparation method is consistent with that of Example 1, except that the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer in Comparative Example 1 is 1:0.
[0112] Comparative Example 2
[0113] The preparation method is consistent with that of Example 1, except that the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer in Comparative Example 2 is 1:4.
[0114] Comparative Example 3
[0115] The preparation method is consistent with that of Example 1, except that the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer in Comparative Example 3 is 1:4. The sum of the thicknesses of the first dry-process negative electrode layer and the second dry-process negative electrode layer is 60 μm.
[0116] Comparative Example 4
[0117] The preparation method is consistent with that of Example 1, except that the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer in Comparative Example 4 is 5:1. The sum of the thicknesses of the first dry-process negative electrode layer and the second dry-process negative electrode layer is 60 μm.
[0118] Comparative Example 5
[0119] The preparation method is consistent with that of Example 1, except that the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer in Comparative Example 5 is 1:1. The sum of the thicknesses of the first dry-process negative electrode layer and the second dry-process negative electrode layer is 60 μm.
[0120] Comparative Example 6
[0121] The preparation method is consistent with that in Example 1, except that the content of negative electrode active material in the first dry-process negative electrode layer and the second dry-process negative electrode layer in Example 6 is the same, and the second dry-process negative electrode layer does not contain non-fibrous binder, that is, the mass ratio of negative electrode active material, solid electrolyte, conductive agent and fibrous binder in the first dry-process negative electrode layer and the second dry-process negative electrode layer is 49:45:5:1.
[0122] Comparative Example 7
[0123] The preparation method is consistent with that in Example 1, except that the silicon mass content of the negative electrode active materials of the first dry-process negative electrode layer and the second dry-process negative electrode layer in Comparative Example 7 is the same, and the negative electrode active materials are both silicon-carbon alloy 650 with a silicon mass content of 13%.
[0124] Comparative Example 8
[0125] The preparation method is consistent with that of Example 1, except that the negative electrode active materials of the first dry-process negative electrode layer and the second dry-process negative electrode layer in Comparative Example 8 are both large-particle negative electrode active materials, with D50=13 μm.
[0126] Performance Testing Methods
[0127] Under 25°C environment, the all-solid-state lithium-ion batteries prepared in Examples 1 to 12 and Comparative Examples 1 to 8 were subjected to long-cycle charge and discharge after being capacitated, and the number of normal temperature cycle circles was measured; the test conditions were as follows: the all-solid-state lithium-ion batteries were subjected to long-cycle charge and discharge tests after being capacitated, and the first-cycle capacitated discharge specific capacity and the number of normal temperature cycle circles when the SOH was 50% were recorded during the process; the operating voltage range was -0.615 to 1.4V, the capacitated ratio was 0.1C, and the normal temperature cycle test ratio was 0.3C.
[0128] The test results are shown in Table 1 below.
[0129] Table 1. Performance test results of all-solid-state lithium-ion batteries of Examples 1 to 15 and Comparative Examples 1 to 8
[0130]
[0131]
[0132]
[0133] It can be seen from Examples 1 to 5 and Comparative Examples 1 to 5 that when a gradient-designed all-solid-state dry-process negative electrode sheet is used, that is, a first dry-process negative electrode layer and a second dry-process negative electrode layer are used, the mass content of the first fibrous binder in the first dry-process negative electrode layer is 1%-2%, and the mass content of the non-fibrous binder in the second dry-process negative electrode layer is 0.6%-4%, especially when the mass ratio of the fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is 1:1.5-4, which can be selected as 1:1.5-3.2, and especially the ratio is in the range of 1:2-3, and the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is in the range of 1:1-2, and at the same time, the ratio of the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer to the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1.4-1.6, which can effectively improve the number of normal temperature cycles of the battery, thereby improving the battery performance and cycle stability. As can be seen from Comparative Examples 1-2, when the mass ratio of the fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is not within the above range (i.e., the mass ratio is 1:0 and 1:5), the cycle performance of the battery deteriorates, and the number of cycles at room temperature decreases significantly. This is because the interface in the second dry-process negative electrode layer away from the negative electrode current collector is more prone to debonding, thereby deteriorating the performance of the all-solid-state battery. In addition, as can be seen from Comparative Examples 3 to 5, when the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is not within the above range (1:1 to 2), the cycle performance of the battery deteriorates, and the number of cycles at room temperature decreases significantly; for Comparative Example 3, this is because the high content of the insulating binder (PTFE and PVDF) in the second dry-process negative electrode layer leads to limited ion transport inside the all-solid-state dry-process negative electrode sheet; for Comparative Examples 4 and 5, this is because the thinner second dry-process negative electrode layer cannot completely make the interface durability of the components inside the all-solid-state dry-process negative electrode the same throughout the thickness, resulting in partial debonding of the interface, thereby deteriorating the performance of the corresponding all-solid-state battery.
[0134] It can be seen from Example 1 and Examples 6-8 that when the mass content of the first negative electrode active material is W1 and the mass content of the second negative electrode active material is W2, W1 is 40%~60%, and W1:W2 is in the range of 1:1~1.3, and the mass ratio of the first negative electrode active material, solid electrolyte, conductive agent and first fibrous binder in the first dry-process negative electrode layer is in the range of (40~60): (30~50): (1~10): (1~2), and the mass ratio of the second negative electrode active material, solid electrolyte, conductive agent and second fibrous binder to non-fibrous binder in the second dry-process negative electrode layer is in the range of (40~60): (30~50): (1~10): (1~5), the performance and cycle stability of the all-solid-state battery can be effectively improved.
[0135] It can be seen from Example 1 and Examples 10-11 and Examples 15 and 16 and Comparative Examples 6 to 8 that the above negative electrode active material content ratio and negative electrode active material silicon content ratio are adopted in the first dry-process negative electrode layer and the second dry-process negative electrode layer, and a compounding strategy of large and small particle negative electrode active materials is adopted in the second dry-process negative electrode layer, that is, the negative electrode active materials in the second dry-process negative electrode layer are silicon-carbon alloy with a higher silicon doping amount and silicon carbon with a small particle size, the D50 of the silicon-carbon alloy with a higher silicon doping amount is 12-14 μm, the D50 of the silicon carbon with a small particle size is 7-9 μm, and the ratio of the silicon mass content of the silicon-carbon alloy with a lower silicon doping amount (in the range of 10%-30%) and the silicon-carbon alloy with a higher silicon doping amount is 1:1.8-2.2 (see Examples 15 and 16), the surface capacity of the dry-process negative electrode layer and the utilization rate of the negative electrode active material can be greatly improved, thereby improving the energy density of the battery. At the same time, designing a reasonable mass ratio of fibrous binder to non-fibrous binder in the second dry-process negative electrode layer and adjusting the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer can improve the battery energy density while promoting the uniformity of the reaction kinetics in the depth direction of the negative electrode, making the interface durability of each component inside the all-solid-state dry-process negative electrode the same throughout the thickness, thereby improving battery performance and cycle stability.
[0136] In addition, it can be seen from Examples 12-14 that when the D50 of the solid electrolyte is 2~4μm, the performance and cycle stability of the all-solid-state battery can be effectively improved.
[0137] The features of several embodiments are summarized above so that those skilled in the art can better understand various aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for performing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that such equivalent constructions do not deviate from the spirit and scope of the present invention, and that they can make various changes, substitutions and modifications herein without departing from the spirit and scope of the present invention.
Claims
1. An all-solid-state dry-process negative electrode sheet, characterized in that: include: Anode current collector; A first dry-process negative electrode layer, disposed close to the negative electrode current collector; as well as The second dry-process negative electrode layer is arranged relative to the first dry-process negative electrode layer and is far away from the negative electrode current collector. wherein the first dry-process negative electrode layer comprises a first fibrous binder, and the second dry-process negative electrode layer comprises a second fibrous binder and a non-fibrous binder, Wherein, the first dry-process negative electrode layer includes a first negative electrode active material, and the second dry-process negative electrode layer includes a second negative electrode active material, the first negative electrode active material includes a silicon-carbon alloy with a first silicon doping amount, the second negative electrode active material includes a silicon-carbon alloy with a second silicon doping amount and a third silicon-carbon alloy, and wherein, based on the mass of the silicon-carbon alloy with the first silicon doping amount, the mass content of silicon in the silicon-carbon alloy with the first silicon doping amount is W3, and based on the mass of the silicon-carbon alloy with the second silicon doping amount, the mass content of silicon in the silicon-carbon alloy with the second silicon doping amount is W4, wherein W3 is 10%-30%, and W3:W4 is 1:1.8~2.
2.
2. The all-solid-state dry-process negative electrode sheet according to claim 1, characterized in that: The mass content of the first fibrous binder in the first dry-process negative electrode layer is 1%-2%; The mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is 1:1.5-4, wherein the mass content of the non-fibrous binder in the second dry-process negative electrode layer is 0.6%-4%; and The thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1-2.
3. The all-solid-state dry-process negative electrode sheet according to claim 2, characterized in that: The mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is 1:1.5-3.2; and / or, The ratio of the mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer to the thickness ratio of the first dry-process negative electrode layer to the second dry-process negative electrode layer is 1:1.4-1.
6.
4. The all-solid-state dry-process negative electrode sheet according to claim 1, characterized in that: in, Based on the mass of the first dry-process negative electrode layer, the mass content of the first negative electrode active material is W1, and based on the mass of the second dry-process negative electrode layer, the mass content of the second negative electrode active material is W2, wherein W1 is 40%~60%, and W1:W2 is 1:1~1.
3.
5. The all-solid-state dry-process negative electrode sheet according to claim 4, characterized in that: in, The first silicon doping amount is less than the second silicon doping amount.
6. The all-solid-state dry-process negative electrode sheet according to claim 5, characterized in that: The particle size of the second silicon-doped silicon-carbon alloy is larger than the particle size of the third silicon-carbon alloy. Wherein, in the volume-based particle size distribution, the particle size of the silicon-carbon alloy with the first silicon doping amount, starting from the small particle size side and reaching 50% of the volume accumulation, is 12 μm to 14 μm; In the volume-based particle size distribution, the particle size of the silicon-carbon alloy with the second silicon doping amount, starting from the small particle size side and reaching 50% of the volume accumulation, is 12 μm to 14 μm; and In the volume-based particle size distribution, the particle size of the third silicon-carbon alloy is 7 μm to 9 μm from the small particle size side to reach 50% of the volume accumulation. The all-solid-state dry-process negative electrode plate further comprises a solid electrolyte, wherein, in the volume-based particle size distribution, the solid electrolyte has a particle size of 2 μm to 4 μm starting from the small particle size side and reaching 50% of the volume accumulation.
7. The all-solid-state dry-process negative electrode sheet according to claim 2, characterized in that: The mass ratio of the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is 1:2-3.
8. The all-solid-state dry-process negative electrode sheet according to claim 4, characterized in that: The first dry-process negative electrode layer and the second dry-process negative electrode layer further include a solid electrolyte and a conductive agent. The mass ratio of the first negative electrode active material, the solid electrolyte, the conductive agent and the first fibrous binder in the first dry-process negative electrode layer is 40-60:30-50:1-10:1-2, and the mass ratio of the second negative electrode active material, the solid electrolyte, the conductive agent and the second fibrous binder to the non-fibrous binder in the second dry-process negative electrode layer is 40-60:30-50:1-10:1-5; The non-fibrous binder includes at least one of sodium carboxymethyl cellulose, LA type aqueous electrode binder, styrene-butadiene rubber, sodium alginate, polyacrylonitrile, polyurethane, polyacrylic acid or polyvinylidene fluoride; The fibrous binder includes at least one of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, polypropylene, polyethylene, ethylene-octene copolymer or polyimide.
9. An all-solid-state battery, characterized in that: It comprises the all-solid-state dry-process negative electrode plate according to any one of claims 1 to 8.
Citation Information
Patent Citations
Negative electrode sheet, secondary battery, and electronic device
CN116111046A
Negative plate, preparation method thereof and device using negative plate
CN116825963A
All-solid-state soft package battery
CN117374373A
Positive pole piece, preparation method thereof and lithium ion battery
CN117613239A
Solvent-free methods of forming solid state electrodes with polymer fiber networks and solid state electrodes made therefrom
CN117691048A